Descriptive Study of Students’ Understanding of The Competencies of Physical Education Teachers - Syafruddin , Muhammad Akbar; Ikadarny, Ikadarny (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This research is a descriptive study which aims to determine the level of understanding of the 2019 FIKK UNM Physical Education, Health and Recreation Study Program students regarding teacher competency. The data collection technique was carried out by surveying 50 students. Data collection was carried out with a questionnaire of 50 questions using the Guttman scale. Analysis uses descriptive tests which are then grouped into 5 (five) categories. Based on the research results, it is known that the understanding of the students of the Physical Education, Health and Recreation Study Program FIKK UNM, namely 5 people or 10% are in the "very poor" category, 10 people or 20% are in the "poor" category, 17 people or 34% are in the medium category, 18 people or 35% were in the "good" category, and none were in the very good category. So it can be concluded that the majority of students' understanding of teacher competency is in the "good" category.